Global aspects of reputation and strategic management - Deephouse, David; Gardberg, Naomi; Newburry, William (Research in global strategic management ;, 2019)
Growing tensions and disagreements over globalization, as well as the role of multinational enterprises in the global economy, and competition among countries, has made the challenge of managing reputation across national institutional environments increasingly complex. Global Aspects of Reputation and Strategic Management addresses these critical strategic issues by exploring how country-level factors influence reputation development and how reputation obtained in one context can be transferred to another. This volume of Research in Global Strategic Management addresses three broad themes - Managing a Global Reputation, National Context and Reputation, and Approaches to Reputation Measurement - and identifies opportunities for future research on global aspects of reputation and strategic management to inspire and strengthen this key area. The complexity resulting from this multi-level exploration of reputation makes illuminating reading for researchers and scholars in the areas of international business, strategy and management, as well as for practitioners wanting to develop and implement an international strategy.